Interdisciplinariedad, autonomía e identidad de la ciencia política en Colombia: la apuesta de la Universidad de Antioquia. (2020)
This article exposes the role of interdisciplinarity in political science in Colombia, addressing the undergraduate degree in political science at the University of Antioquia as an illustrative reference on the subject. Firstly, the history of the discipline in Colombia is developed, deepening the discussions around hybridization and interdisciplinarity. It is concluded that the former is problematic in terms of autonomy and disciplinary identity, while the latter enables an opening to dialogue with the other social sciences and delimits disciplinary boundaries that allow for clarity about their field of specialization. On the other hand, the strengths and challenges of the consolidation of the discipline at the University of Antioquia are identified. The need to open and maintain disciplinary discussion spaces is emphasized, where minimum procedures can be defined for this interdisciplinary dialogue.